Osteoporosis: An Underdiagnosed Problem in Patients with Ankylosing Spondylitis - Yeşim Kirazlı; Ece Çınar (Galenos Yayinevi, 2022)
Patients with ankylosing spondylitis (AS) are at an increased risk of osteoporosis (OP) and subsequent osteoporotic fractures due to bone fragility. Although AS is a risk factor for developing new-onset OP, there are no existing guidelines to routinely assess patients with AS for OP, and young men are less likely to be screened. Given that the underestimation of OP in patients with AS can have serious health consequences, a greater emphasis should be placed on this association. Major risk factors for vertebral fractures in AS include low bone mineral density (BMD) at the femoral neck and total hip (but not lumbar spine), male sex, longer disease duration, higher disease symptom scores, inflammatory bowel disease, and structural severity of the disease. The major pathophysiological mechanisms for osteoporosis appear to be systemic inflammation and low BMD resulting from decreased daily physical activity caused by pain, stiffness, and ankyloses. The weight of evidence is strongly in favor of the interleukin (IL)-17-IL-23 axis, tumor necrosis factor-α and gut immunopathobiology as central components affecting bone in AS.